Host-Guest Complexes of Dodeka(ethylene)octamine: Prediction of Ion Selectivity by Quantum Chemical Calculations IX - Puchta, Ralph; Walther, Daniel; März, Matthias; Begel, Svetlana; van Eldik, Rudi (Zeitschrift für Anorganische und Allgemeine Chemie, 2019)
In this contribution we investigated the ion complexation of Bühl's cryptand, dodeka(ethylene)octamine by quantum chemical methods (B3LYP/LANL2DZp). This cryptand is an isomer of a well-known Lehn-type cryptand [TriPip222]. The ion selectivity was determined based on the energetic criteria derived by model reactions starting from solvated metal ions and empty dodeka(ethylene)octamine, and by comparing the M–N bond length in [M ⊂ dodeka(ethylene)octamine]m+ and [M(NH3)6]m+. We calculated that Bühl's cryptand will complex best Na+ followed by Li+ as alkaline cations and Ca2+ followed by Mg2+ as alkaline earth metal ions. Based on this data we conclude that Bühl's cryptand offers a smaller cavity to nest ions than the Lehn-type [TriPip222].
CRIS-Team Scopus Importer:2019-06-18
Keywords: Cryptands; DFT study; Selective ion complexation